2015
DOI: 10.1111/ajt.13318
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Engineered Tracheal Replacement in a Child: A 4-Year Follow-Up Study

Abstract: In 2010, a tissue‐engineered trachea was transplanted into a 10‐year‐old child using a decellularized deceased donor trachea repopulated with the recipient's respiratory epithelium and mesenchymal stromal cells. We report the child's clinical progress, tracheal epithelialization and costs over the 4 years. A chronology of events was derived from clinical notes and costs determined using reference costs per procedure. Serial tracheoscopy images, lung function tests and anti‐HLA blood samples were compared. Epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
147
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(149 citation statements)
references
References 22 publications
0
147
0
2
Order By: Relevance
“…of some interventions, and an inability to study cell fate in humans means that little is known about their contribution. Clinical observations showed that patients were slow to regenerate healthy mucosa (3,4,15,16). High cell-seeding densities are required for bioengineering applications and, given the large surface area of clinical tracheal grafts, obtaining sufficient numbers of autologous epithelial cells is a challenge for the field.…”
mentioning
confidence: 99%
“…of some interventions, and an inability to study cell fate in humans means that little is known about their contribution. Clinical observations showed that patients were slow to regenerate healthy mucosa (3,4,15,16). High cell-seeding densities are required for bioengineering applications and, given the large surface area of clinical tracheal grafts, obtaining sufficient numbers of autologous epithelial cells is a challenge for the field.…”
mentioning
confidence: 99%
“…Aside from the work performed by the Macchiarini group, two pediatric patients have undergone treatment with tissue engineered tracheal conduits (26,28,29). Both patients suffered from severe congenital airway defects and had undergone multiple prior corrective procedures.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Notwithstanding these issues, tracheal tissue engineering raises fewer potential ethical objections as an experimental therapy than in other clinical niches, given the total lack of alternative treatment options, and the greater intrinsic regenerative potential of pediatric patients compared to adults increases the likelihood of success. As such, regenerative approaches in the trachea have outstripped other organs in terms of high profile clinical compassionate cases both in adults [23], and in children [24,25].…”
Section: Concept Of Tissue Engineeringmentioning
confidence: 99%